2015
DOI: 10.1111/jgh.12710
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin's therapeutic effect: Suppressing Th1/Th17 simultaneously in a mouse model of Crohn's disease

Abstract: Oridonin is a potential modulator for trinitrobenzene sulfonic acid-induced colitis and other Th1/Th17 mediated inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Moreover, oridonin pretreatment inhibits the release of pro-inflammatory mediators, including nitric oxide, TNF alpha, IL-1 beta, and IL-6, resulting in the inhibition of the DNA-binding activity of NF-kappa B [ 45 ]. Oridonin is also reported to be a potential modulator for trinitrobenzene sulfonic acid-induced colitis and other Th1/Th17-mediated inflammatory diseases [ 108 ].…”
Section: Immunomodulatory Effectsmentioning
confidence: 99%
“…Moreover, oridonin pretreatment inhibits the release of pro-inflammatory mediators, including nitric oxide, TNF alpha, IL-1 beta, and IL-6, resulting in the inhibition of the DNA-binding activity of NF-kappa B [ 45 ]. Oridonin is also reported to be a potential modulator for trinitrobenzene sulfonic acid-induced colitis and other Th1/Th17-mediated inflammatory diseases [ 108 ].…”
Section: Immunomodulatory Effectsmentioning
confidence: 99%
“…Th1 cells, the chief mediators in type 1 immunity, can secrete interferon-γ (IFN-γ) (the iconic product of Th1 cells), interleukin 12 (IL-12), and tumor necrosis factor-α (TNF-α) which, in turn, induce TNF-α, IL-6, and IL-1β to release from macrophages. Wang et al have found that the clinical course of CD-like mouse colitis has been improved by inhibiting the activation of Th1/Th17 cells [ 15 ]. The activated Th2 cells and the cytokines secreted by Th2 cells, such as IL-4, IL-5, IL-9, IL-10, IL-23, and IL-25, have increased in inflamed mucosa of UC patients than in CD ones [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oridonin, an ent-kaurane diterpenoid isolated from Rabdosia rubescens (Donglingcao), has various pharmacological and biological properties such as anti-inflammatory, antiviral, and antibacterial activities [8]. Many studies have suggested that oridonin has potent anticancer activity against several cancers, including lung cancer, colorectal cancer, and hepatocellular carcinoma, in vitro and in vivo [9][10][11][12] and may exert beneficial effect against Alzheimer's disease [13], acute lung injury [14], postinflammatory irritable bowel syndrome [15], and Crohn's disease [16]. ese diseases are closely related to inflammation.…”
Section: Introductionmentioning
confidence: 99%